Women's economic gains from employment, marriage and cohabitation - Alita Nandi (University of Essex, Institute for Social and Economic Research (ISER), 2008)
U.S. public policy promotes both marriage and labor market participation as strategies for improving the economic welfare of low-income women and their children. Here I compare womens economic gains from marriage, cohabitation and employment. Using data from the NLSY79, I estimate a fixed-effects model of household income (adjusted for household composition). I find that among poor women (those who ever received welfare), the log household income of single, nonemployed women would increase by 0.80 if they enter a cohabiting union, 1.04 if they marry, 0.76 if they work part-time (1000 hours/year), and 1.16 if they work full-time (2000 hours/year).
Keywords: 330